PENGARUH ORIENTASI KEPEMIMPINAN, MOTIVASI DAN KOMUNIKASI TERHADAP EFEKTIVITAS KERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGAH - Gunarto, Moh. (Katalogis, 2016)
The objectives of this research are : 1) to seek and analyze the simultaneous influence of leadership orientation, motivation, and communication on work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Provience; 2) to seek and analyze the influence of leadership orientation on work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province; 3) to seek analyze the influence of motivation on work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province; 4) to seek and analyze simultaneous influence of communication on work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province. The research is quantitative descriptive that shows the relationship between the variabels studied and it involves 140 respondents who selected through proportional random sampling. Based on multiple linear regressions analysis,the result show that: 1) leadership orientation,motivation, and communication simultaneously influence work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province; 2) leadership orientation significantly influences work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province; 3) motivation significantly influences work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province; 4) communication significantly influences work effectiveness of officials in The Department of Manpower and Transmigration, Central Sulawesi Province.